"Труди і дні" Валерія Шевчука (до 80-ліття від дня народження) - Мовчан, Р.В. (Слово і Час, 2019)
У статті йдеться про класика української літератури ХХ ст. Валерія Шевчука – письменника (поета, прозаїка, драматурга), історика-культуролога, літературознавця, упорядника-архівіста, перекладача, мемуариста, представника київського шістдесятництва, лідера “житомирської прозової школи”, предтечі українських постмодерністів та про його різногранну літературну творчість. Увагу зосереджено на її витоках, метафізичній пов'язаності з містами Житомиром і Києвом, із українською бароковою традицією. Здійснено огляд особливостей його індивідуального стилю, великої історико-літературної, культурологічної діяльності та її значення в національному гуманітарному просторі. The essay is focused on the classic of the 20th century Ukrainian literature Valerii Shevchuk and his complex and diverse literary work in various genres. He is a writer (poet, prose writer, play writer), historian of culture, literary scholar, archivist, translator, memoirist, prominent representative of Kyiv Sixtiers, leader of ‘Zhytomyr prose school’ and forerunner of Ukrainian postmodernists. Special attention is paid to the sources of the author’s work, its metaphysical connection with Zhytomyr where he was born, and Kyiv where he has been living and writing and endured a decade of forced solitude remaining free, where he truly established himself as a Ukrainian writer. His research activity and translation work, focused on Ukrainian history and Old Ukrainian literature (particularly of the 16th–18th centuries), provoked the writer’s interest in Ukrainian Baroque tradition and its transformation in his own works. It all started with poetry, which he never stopped writing. That is why the subjective stuff is also important in his prose, which is rational in its neo-baroque basis. The essay provides a general overview of the specific features of Shevchuk’s individual style, which is characterized by combination of realistic authenticity with convention or irreality, ‘high’ and ‘low’ narration style, travesty of storylines and images, parabolic technique, historiosophy, irony, etc. Worthy of separate attention and high esteem is the scholarly work of the writer and his contribution to the general field of culture. This activity includes preparation of different anthologies and collections, numerous translations of Kyivan Rus texts into modern Ukrainian, many articles, prefaces, extensive historical and cultural studies, etc. The work of Valerii Shevchuk is important for the humanities and promotes self-consciousness and self-empowerment of Ukrainians, as well as their communication with the world cultural heritage.